Modulation and control of multilevel inverter for an open‐end winding induction motor with constant voltage levels and harmonics. Issue 1 (1st January 2017) - Mahato, Bidyut; Raushan, Ravi; Jana, Kartick Chandra
Abstract : A multilevel inverter (MLI) with staircase waveform having maximum number of voltage levels at any desired voltage (or frequency) of a variable voltage, variable frequency application can play an important role in the modern power conversion system. In most of the control and modulation techniques of MLI, the number of voltage level reduces with the reduction of modulation index that increases the harmonic and total harmonic distortions (THDs). The variable voltage application of MLI using a single DC source of variable magnitude is the elementary concept of the proposed control technique. A cascaded MLI having unequal voltage sources with controlled magnitude can be used to increase the number of voltage levels. The closed‐loop voltage control technique and a multi‐winding transformer‐rectifier based AC‐link system is used to obtain the multiple variable voltage DC sources for the cascaded MLI. A nearest level modulation based control technique has been implemented for the MLI to obtain the fixed level voltage waveforms with constant THD and reduced switching losses. The whole control algorithm for a nine‐level inverter is simulated and results are experimentally verified on a laboratory prototype of the three‐phase induction motor drives.